Research on Wet Etching Techniques for GaInAs/AlInAs/InP Superlattices in Quantum Cascade Laser Fabrication - Shiya Zhang; Lianqing Zhu; Han Jia; Bingfeng Liu; Jintao Cui; Tuo Chen; Mingyu Li (Nanomaterials)
Wet etching is the mainstream fabrication method for single-bar quantum cascade lasers (QCLs). Different etching solutions result in varying etching effects on III-V semiconductor materials. In this study, an efficient and nearly ideal etching solution ratio was proposed for simultaneously etching both InP and GaInAs/AlInAs, and the surface chemical reactions induced by each component of the etching solution during the process were investigated. Using univariate and single-component experiments, coupled with various characterization techniques such as atomic force microscopy (AFM), stylus profilometer, X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), we found that the ratio of HBr to hydrogen peroxide significantly determines the etching rate, while the ratio of HCl to hydrogen peroxide affects the interface roughness. The aim of this study was to provide a comprehensive understanding of the effects of different etching solution components, thereby enhancing the understanding of the wet etching process for InP/GaInAs/AlInAs materials. These findings offer valuable insights into efficient QCL fabrication processes and contribute to the advancement of the field.